Lipid nanocarriers : a novel approach to delivering ophthalmic clarithromycin - Makoni, Pedzisai Anotida (Rhodes University, Faculty of Pharmacy, Pharmacy, 2021)
The feasibility of incorporating clarithromycin (CLA) into innovative solid lipid nanoparticles (SLN) and nanostructured lipi d carriers (NLC) using hot emulsification ultrasonication (HEUS) was investigated. This approach was investigated in an attempt to address the shortcomings associated with the use of lyophilized parenteral formulations administered via the ocular route suc h as toxic reactions, intolerance and patient discomfort due to frequent insti llation of topical solutions of CLA. In particular, sustained release approaches to delivery may enhance precorneal retention, increase ocular availability and permit dose reduction or use of a longer dosing frequency when treating ocular non - tuberculous m ycobacterial (NTM) keratitis infections. This approach may potentially improve the delivery of CLA to the eye, thereby addressing some or all of the unmet clinical needs described vide infra . Prior to initiating pre - formulation, formulation development a nd optimization studies of CLA - loaded SLN and/or NLC, Design of Experiments (DoE), specifically a Central Composite Design (CCD) was used in conjunction with Response Surface Methodology (RSM) to develop and optimize a suitable method for the quantitative determination of CLA in pharmaceutical formulations and for monitoring CLA release from SLN and/or NLC in vitro . A simple, accurate, precise, sensitive and stability - indicating reversed phase - high performance liquid chromatography (RP - HPLC) method with ele ctrochemical (EC) detection was developed, validated and optimized for the in vitro analysis of CLA loaded SLN and/or NLC formulations. Pre - formulation studies were undertaken to investigate the thermal stability of CLA and bulk lipids to facilitate the s election of lipid excipients for the manufacture of nanocarriers in addition to establishing compatibility of CLA with the excipients. It was established that CLA was thermostable up to a temperature of approximately 300 Â°C thereby indicating that HEUS cou ld be used for the manufacture of CLA - loaded SLN and/or NLC. Lipid screening revealed that CLA i s, in general, poorly soluble in solid and liquid lipids however a combination of stearic acid (SA) and Transcutol Â® HP (THP) exhibited the best dissolution pote ntial for CLA of all lipids tested . Stearic acid appears to exist as polymorphic form B prior to exposure to heat however occurs as the form C polymorph following heating at 85 Â°C for one hour. The best ratio for the mixture of SA and THP for the manufactu re of CLA - NLC ii was an 80:20 ( w/w ) ratio of SA: THP as the two lipids are miscible in this ratio and exhibited the greatest dissolution potential for CLA. Furthermore, an investigation of binary mixtures of CLA/SA and SA/Transcutol Â® HP, in addition to eutect ic mixtures of CLA, SA and Transcutol Â® HP, revealed no obvious interaction between CLA and the lipids selected for the production of the nanocarriers. Due to the relatively high solubility of CLA in THP in comparison to SA, NLC are likely to exhibit a hig her loading capacity (LC) and encapsulation efficiency (EE) for CLA than SLN. Consequently the feasibility of incorporating CLA (10% w/w ) into NLC was investigated and evaluation of the production of SLN was not undertaken as the production of these might not result in the manufacture of a delivery technology with a high EE and LC for CLA. Tween Â® 20 was used as the surfactant as it is readily available, exhibits little or no cytotoxicity and is relatively cheap. Polyethylene glycol (PEG) was used as a coati ng polymer to impart muco - adhesive properties the formulated CLA - NLC. Response surface methodology (RSM) in conjunction with DoE, specifically a Box - Behnken Design (BBD) used as a screening design was used to identify a formulation composition which would produce a product that would meet the pre - defined target critical quality attributes (CQA) for the nanoparticles viz. particle size (PS) in the nano - range, polydispersity index (PDI) < 0.5, Zeta Potential (ZP) â‰¥ Â± 30 mV, and EE > 80%. The formulation composition identified was subsequently used for the optimization of the manufacturing parameters viz. sonication time and amplitude, using a Central Composite Design (CCD) . The LC and EE, in vitro CLA release, cytotoxicity, osmolarity, pH, degree of crystallinity and lipid modification, elemental analysis and surface morphology of the optimized batch was investigated and mon itored to ensure that CLA - loaded NLC, of the desirable quality, had been produced. On the day of manufacture the mean PS and PDI of the optimized CLA - loaded NLC formulation adjusted to physiological osmolarity (250 "“ 450 mOsm/kg) was 461.9 Â± 40.16 nm and 0. 523 Â± 0.104, respectively. The ZP for the optimized NLC generated on the day of manufacture using HPLC grade water as the dispersion medium was - 20.5 Â± 4.82 mV. The pH and osmolarity of the optimized CLA - loaded NLC formulation was 7.76 Â± 0.01 and 316 Â± iii 2 m Osm/Kg, respectively and the EE was 88.62 Â± 0.23 %. The optimized NLC exhibited a decreased crystallinity in comparison to the bulk lipid materials. DSC, WAXS and FT - IR revealed that CLA was molecularly dispersed in the nanocarriers. The optimized CLA - load ed NLC exhibited muco - adhesive properties, when tested under stationary conditions using laser doppler anemometry (LDA). The optimized formulation also exhibited sustained release of CLA over 24 hours during in vitro release testing and CLA release was bes t described using the Baker - Lonsdale model . The cumulative % CLA released over 24 hours was 56.13 Â± 0.23% and mass balance analysis revealed 41.38 Â± 0.02% CLA had been retained in the NLC. In vitro cytotoxicity testing revealed that the optimized CLA - NLC w ere less cytotoxic to HeLa cells when compared to CLA alone and further confirmed that the lipids and excipients used in these studies were of GRAS status . Stability studies revealed that the EE reduced over 28 days by 14.42% and 5.14% when stored at 4 Â°C and 22 Â°C , respectively. In addition, the particle size increased from the nm to Î¼m range for samples stored at 22 Â°C. The findings are a good starting point but require further optimization to ensure prolongation of stability. In addition , the technology requires additional developmental studies and a powder for reconstitution for use as a single - dose considered as single dose packaging may be a solution to the compromised formulation stability observed in these studies. The CLA - NLC produced in these stu dies exhibit sound product attributes which serve as a useful foundation for the novel delivery of antibiotics to the eye. The results suggest that the optimized NLC have the potential to enhance precorneal retention and increase ocular availability of CLA , which in turn may be useful to reduce the required dose and dosing frequency when administering CLA as a reconstituted solution to treat susceptible organisms that infect ocular tissues.
Keywords: Clarithromycin; Nanomedicine; Nanostructures; Antibiotics; Eye -- Diseases -- Treatment; Ocular pharmacology; Ophthalmic drugs; Karatitis -- Chemotherapy